Analisis Teori Transparansi Pengelolaan Keuangan Daerah di Indonesia - Nurhayati Nurhayati (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan ilmu Politik Universitas Riau Kep, 2017)
Abstract The purpose of transparency is to provide open financial information for the community in order to realize good governance. in order to realize the good governance in relation to the implementation of regional autonomy, it is necessary to reform the management of regional finance and state financial reform. The implementation of regional autonomy in its entirety brings logical consequences in theform of governance and development based on sound financial management.Transparency will ultimately create horizontal accountability between local governments and communities in order to create clean, effective, efficient, accountable and responsive local governance of community aspirations and interests. The facts show that in the management of local budget / finance as if still compiled with the concept of less mature / perfect, in a hurry and finally born prematurely or not well. Regulations that are born prematurely certainly contain various weaknesses and deficiencies and even lack of direction. Moreover, if born in the condition of high political temperature that is the war of interest among agencies who feel authorized to regulate it so that the level of transparency of financial management, especially at the regional level still contains a lot of uncertainty and indecision in providing guidance to the direction of local financial management policy. This has resulted in confusion among local governments in managing their finances. Keywords: analysis, regional finance and transparency Abstrak Tujuan transparansi adalah menyediakan informasi keuangan terbuka bagi masyarakat dalam rangka mewujudkan penyelenggaraan pemerintahan yang baik (Good Governance). dalam rangka mewujudkan good governance tersebut dalam kaitannya dengan pelaksanaan otonomi daerah, maka diperlukan reformasi pengelolaan keuangan daerah dan reformasi keuangan negara. Penerapan otonomi daerah seutuhnya membawa konsekuensi logis berupa penyelenggaraan pemerintahan dan pembangunan berdasarkan manajemen keuangan yang sehat. Pada dasarnya penerapan prinsip transparansi keuangan sangat membantu penyusunan anggaran pemerintah daerah (RAPBD) yang objektif dan berkualitas. Prinsip akuntabilitas dan transparansi keuangan diyakini dapat mendukung usaha mewujudkan pilar-pilar penyelenggaraan pemerintahan yang bersih dan berwibawa. Tingkat transparansi pengelolaan keuangan khususnya di tingkat daerah masih banyak mengandung ketidakjelasan dan ketidaktegasan dalam memberikan pedoman kepada arah kebijakan pengelolaan keuangan daerah. Hal ini mengakibatkan kebingungan pemerintah daerah dalam pengelolaan keuangannya. Kata kunci: analisis, keuangan daerah dan transaparansi